Resting-state connectivity alterations during transient global amnesia - Zidda, Francesca; Griebe, Martin; Ebert, Anne; Ruttorf, Michaela; Roßmanith, Christina; Gass, Achim; Nees, Frauke; Szabo, Kristina (NeuroImage: Clinical, 2019)
While the pathophysiology of transient global amnesia (TGA) is not understood, due to the specific nature of the clinical deficits, transient dysfunction in the medial temporal lobe, especially in the hippocampus, is assumed; however, concomitant disturbances in other brain regions and in executive function have been postulated. In this study, a cohort of 16 patients was prospectively recruited from the emergency department for resting-state functional MRI (fMRI) during the acute stage of TGA, as confirmed by a standardized neuropsychological assessment. Twenty age- and sex-matched controls, as well as twenty patients with a history of TGA, were recruited for comparison. Functional data were processed using independent component analysis (ICA), allowing the complete automatic (data-driven) identification of spontaneous network dynamics. We documented a severe disturbance in anterograde episodic long-term memory in all patients. Group-based ICA of resting-state data in acute TGA patients versus that of controls and patients with a past TGA episode demonstrated reduced FC mainly of structures belonging to the executive network (EN), but also the hippocampus, confirming its pathophysiological involvement in the disorder, as well as areas belonging to the salience network and other subcortical regions. No significant differences were found when comparing connectivity in patients with a history of TGA and controls. Our findings strengthen previous empirical and theoretical accounts of hippocampal and executive dysfunction in TGA. The disruption of frontal, parietal and insular control regions, together with disruption in the hippocampus, provides a new interpretation for the pathophysiology and neuropsychological profile of this neurological disorder on a large-scale network level
Gesehen am 29.11.2019